Формування еліти в середовищі студентської молоді - Кислова, О.Н.; Лисица, Н.М.; Скорынина, О.В. (Український інститут соціальних досліджень імені Олександра Яременка, 2005)
The article deals with the possible sequence of development of sociology of elite on the basis of phases of studying the process of forming of elite in the students environment. The authors define the field of elite and prove that this process consists of phases. The authors point of view is given on the interpretation of elite, the components of contents of elite are presented.
Keywords: еліта; студентська молодь